Fuzzy time series forecasting in determining inventory policy for a small medium enterprise (SME) company - S.Sarifah Radiah Shariff; Nurul Nadiah Abdul Halim; Siti Meriam Zahari; Zuraidah Derasit (Institute of Advanced Engineering and Science, 2020)
Fuzzy time series models have been widely used to handle forecasting problems, such as forecasting consumer demand and production volume. It is of greater benefits if we have good forecasting accuracy rates especially in managing inventory in a Small and Medium Enterprise (SME) company. This study focuses on multiple products with single production line. The aims of this study are to propose the appropriate the forecasting method for the products, to develop new inventory policy that minimizes the total inventory cost for the company. Simple forecasting methods like trend line, three month moving average (MA (3) and fuzzy time series forecasting are used in this study. The result shows that fuzzy time series forecasting model is suitable to be used in forecasting future demand for all products. The proposed inventory policy is based on the number of cycle per year and the number of production for each product has helped the company to minimize total inventory cost and schedule the production process accordingly. The proposed inventory policy resulted in lower total inventory cost when compared to current practice.